Arabic identity in English foreign language classroom conversation: Language selection, patterns, and functions - Salama, Ibrahim; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
Conversation analysis is one of the practical strategies for discourse analysis in speaking that may be used to teach oral English in an English foreign language classroom. Through conversational analysis, this study intends to examine the theoretical foundations of Arabian social identity and the possibility of using a discourse way of speaking to educate a group of learners. The current study focuses on cultural disparities between Arabic-speaking and English-speaking populations, examining the impact of such cultural barriers on Arab-English foreign language learners’ communication. A case study of English foreign language students from the International Arab Egyptian School (IAES) was conducted to achieve this purpose. Using contrastive rhetoric, several challenges in students’ English speaking were explained. Qualitative data analysis of culturally bound distinctions in numerous linguistic features such as letters, vowels, writing style, word use, and syntax, as well as some rhetoric and structural styles such as coordinating, subordinating, and metaphoric styles, revealed the high potential for errors and issues faced by Egyptian EFL students when developing spoken English. Data was collected by recording some sessions and extracting some language from both teachers and students by analyzing the language used inside the classroom. The most significant finding of this research is the organizing training to differentiate the interaction medium in the language classroom. In other words, teachers should use an "interactive decision-making" method in which they must make rapid decisions on which media to use to meet emerging issues such as subject matter comprehension, classroom management, or building a good rapport in the classroom.